Влияние КПД элементов блока преобразования энергии на эффективность цикла модульной ЯЭУ с газоохлаждаемым гелиевым реактором - Халатов, А. А.; Северин, С. Д.; Доник, Т. В. (НТУ "ХПИ", 2015)
Выполнен расчёт термодинамического цикл блока преобразования энергии модульной ядерной энергетической установки с высокотемпературным гелиевым реактором тепловой мощностью 250 МВт в режиме выработки электроэнергии и в комбинированном режиме. Представлен анализ влияния КПД компрессора высокого и низкого давления, гелиевой турбины и степени регенерации теплоты на эффективность цикла ядерной энергетической установки.

One of the promising conceptions for the design of nuclear power stations of the fourth generation is considered to be the conception of a high-temperature gas-cooled reactor that uses helium as an actuating medium. The conversion of the energy of the heated helium into mechanical energy with the subsequent conversion of it into the electric power is performed in the energy conversion block that represents the gas turbine plant consisting of the turbocompressor of a vertical type on electromagnetic bearings with the two-cascade axial compressor, a helium gas turbine and highly efficient heat exchange equipment. This paper describes the computational investigation of the parameters of the thermodynamic cycle of the energy conversion block for the modular nuclear power plant with the high temperature helium reactor having the heat power of 250 MW in the electric power generation mode and in the combined mode of the joint electric power and heat production for the needs of heat supply utilities. The influence of the efficiency factor of some elements of the compressor of high and low pressure and that of the helium turbine and the heat regeneration factor on the efficiency of the cycle of nuclear power plant has been studied.
Influence of the efficiency factor of energy conversion block elements on the cycle efficiency of the modular nuclear power plant (NPP) equipped with the gas cooled helium reactor
Keywords: атомные электростанции; газотурбинная установка; термодинамический цикл; эффективность цикла; modular nuclear power station; gas turbine plant; gas cooled helium reactor; complex thermodynamical cycle; cycle efficiency